Avaliação da exposição materna ao glifosato sobre a homeostase glicêmica da prole adulta de camundongos alimentados ou não com dieta hiperlipídica - Gomes, Ellen Carolina Zawoski (2018)
The use of agrochemicals, such as glyphosate, constituting risk factor for human health and to the environment. The glyphosate is classified as low risk, because the biosynthesis pathway in which it acts in plants, is not present in any member of the animal kingdom. However, several studies have shown the adverse effects of exposure to glyphosate, even at very low doses. The glyphosate has been identified as an endocrine disruptor chemical, which is an exogenous substance that interfering directly with the endocrine system, mimicking the action of natural hormones, and resulting in adverse effects on organisms and/or their progeny. Exposures to the endocrine disruptor chemical at critical times, such as gestation and lactation, may alter the developing trajectory of the fetus, and result in permanent changes in tissues and/or organs. The biological effects observed include, among others, obesity and diabetes. In addition, several studies have shown the effects of direct exposure to glyphosate on glycemic metabolism, however, the results are controversial, even in similar species. Therefore, the present study aims to investigate the effects of maternal exposure to Roundup Original DI®, during pregnancy and lactation, on body parameters, and especially, glucose homeostasis, of adult offspring male mice fed or not with high fat diet. During pregnancy and lactation, female C56BL/6 mice received 0.5% of glyphosate (GL group) in drinking water, while the control group (CTL) received only water. The offspring was named according to the treatment of mothers, and according kind of food, forming the groups: CTL-F1 and GL-F1, fed with standard diet and CTL-HFD-F1 and GL-HFD-F1, fed with high fat diet. At 60 and 90 days of life, male offspring mice were submitted to the glucose tolerance test and the insulin tolerance test. After eight hours fasted, dams and offspring mice were euthanized and body features and fasting glucose and insulin levels were analyzed. The body weight gain during pregnancy and lactation was lower in dams of GF group, without affect the litter size. The dams of GF group also showed lower food and water intake compared to dams of CTL group. Maternal exposure to glyphosate reduced the body weight gain of GF-F1 adult male mice. Also, GL-F1 group showed higher glucose tolerance and insulin sensitivity, without affect fasting blood glucose and insulin, when compared to CTL-F1 group. Pre- and postnatal exposure to glyphosate when associated with high fat diet reduced the body weight gains and the retroperitoneal and perigonadal fat in GF-DH-F1 adult male mice. In addition, GL-HFD-F1 group showed high glucose tolerance and insulin sensitivity, when compared to CTL-HFD-F1 group.